2011
DOI: 10.1029/2010jg001566
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns of land-atmosphere fluxes of carbon dioxide, latent heat, and sensible heat derived from eddy covariance, satellite, and meteorological observations

Abstract: [1] We upscaled FLUXNET observations of carbon dioxide, water, and energy fluxes to the global scale using the machine learning technique, model tree ensembles (MTE). We trained MTE to predict site-level gross primary productivity (GPP), terrestrial ecosystem respiration (TER), net ecosystem exchange (NEE), latent energy (LE), and sensible heat (H) based on remote sensing indices, climate and meteorological data, and information on land use. We applied the trained MTEs to generate global flux fields at a 0.5°×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
1,295
10
11

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,147 publications
(1,434 citation statements)
references
References 79 publications
61
1,295
10
11
Order By: Relevance
“…Our analyses confirmed the latitudinal pattern of AET and its significant relationships with MAP, MAT and vegetation types reported in previous studies (Jung et al, 2011;Brümmer et al, 2012;Xiao et al, 2013). Given the pronounced covariation or interactive effects among climatic factors (e.g., MAT vs. R n , MAT vs, VPD, MAP vs. RH) and vegetation attributes (e.g., MAT vs. LAI, MAP vs. LAI) (Law et al, 2002), it is not surprised that the spatial patterns of AET significantly correlated with that of R n , VPD, RH and LAI.…”
Section: Effects Of Climate and Vegetation On The Spatial Variation Isupporting
confidence: 77%
See 2 more Smart Citations
“…Our analyses confirmed the latitudinal pattern of AET and its significant relationships with MAP, MAT and vegetation types reported in previous studies (Jung et al, 2011;Brümmer et al, 2012;Xiao et al, 2013). Given the pronounced covariation or interactive effects among climatic factors (e.g., MAT vs. R n , MAT vs, VPD, MAP vs. RH) and vegetation attributes (e.g., MAT vs. LAI, MAP vs. LAI) (Law et al, 2002), it is not surprised that the spatial patterns of AET significantly correlated with that of R n , VPD, RH and LAI.…”
Section: Effects Of Climate and Vegetation On The Spatial Variation Isupporting
confidence: 77%
“…Previous studies have demonstrated that the spatial variation in LAI could affect the spatial patterns of different components of AET. For example, evaporation of canopy interception depended on LAI (Jung et al, 2011), and the proportion of AET that evaporated from soil surfaces increased as LAI decreased (Law et al, 2002). Thus, it is seemly that LAI regulates the spatial patterns of AET mainly by influencing the proportion of different AET components (i.e., vegetation transpiration, soil evaporation and evaporation of canopy interception).…”
Section: Effects Of Climate and Vegetation On The Spatial Variation Imentioning
confidence: 99%
See 1 more Smart Citation
“…phenology, LAI) and function (e.g. ET, gross primary productivity) has become increasingly sophisticated (Glenn et al, 2010;Yuan et al, 2010;Jung et al, 2011;Rossini et al, 2012;Kanniah et al, 2013;Ma et al, 2013;Nagler et al, 2013) and increasingly applied to realworld applications of water resources management (Scott et al, 2008;Glenn et al, 2010;Barron et al, 2014;Doody et al, 2014). Remote sensing (RS) provides a robust and spatially explicit means to assess not only vegetation structure and function but also relationships amongst these and climate variables.…”
Section: Satellite-based Approachesmentioning
confidence: 99%
“…These technologies have improved continually with their own appropriate spatiotemporal scales, and researchers have also performed meta-analyses based on multi-source data from different approaches [25,26]. Additionally, comprehensive assessments were conducted on the ecosystem productivity or carbon source/sinks at national, continental and global scales by data-model fusion [7,27,28].…”
Section: Introductionmentioning
confidence: 99%